A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Adapting rodent cued threat conditioning to planarians: Memory acquisition, consolidation, and reconsolidation - Fionnghuala L.J. James; Sayed K. Ahamed; Cheng Yang; Jigme Thinley; Carmelo M. Vicario; Juan J. Canales; Sukhwinder S. Sohal; Richard Wilson; Luke R. Johnson; Vanni Caruso (Behavioural Processes, 2026)

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Spatial ecology of recolonized elk in agricultural landscapes of the Northern Great Plains - Tabitha A. Hughes; Todd Nordeen; Luke Meduna; Sam P. Wilson; John F. Benson (Biological Conservation, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

The Fertilization of Synbiotic Systems in the Intensive Culture of Penaeus vannamei - Otávio Augusto Lacerda Ferreira Pimentel; Wilson Wasielesky; Luis Otavio Brito; Luke Aaron Roy; Nicholas Romano; Dariano Krummenauer (Reviews in Aquaculture, 2025)
Over the years, the intensification of shrimp Penaeus vannamei production has brought challenges such as disease outbreaks and increases in the nutrient loading of effluents. To be more environmentally friendly as production systems intensified, it became necessary to create systems with a high degree of biosecurity and toward efficiency in water and land use. Thus, microbial‐based systems, such as the biofloc, were pioneered to support industry growth and market demand for shrimp. Currently, a derivation of biofloc has emerged and is gaining ground in the shrimp industry, which is the synbiotic system. Synbiotic systems are microbially based and are characterized by fertilizing the culture water with vegetable bran (prebiotics) that were processed by fermentation and/or microbial respiration by probiotic microorganisms. The fertilization strategy creates conditions similar to a natural environment by supporting microbial loop development, controlling water quality, and suppressing harmful, and pathogenic microorganisms. The synbiotic system is still new and without standard fertilization protocols, which has leads to dissimilar results between laboratory research and commercial farms. Therefore, this review is focused on describing the different fertilization procedures used in the synbiotic system for P. vannamei intensive culture, the importance of each fertilizer component, as well as the processing strategies. Furthermore, in this study, we seek to demonstrate perspectives and recommend future research topics to better understand the advantages and disadvantages of this production system.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Real-time classification of ground conditions ahead of a TBM using supervised machine learning algorithms - Sylvanus Sebbeh-Newton; Jamel Seidu; Mawuko Luke Yaw Ankah; Rodney Ewusi-Wilson; Hareyani Zabidi; Louis Amakye (Modeling Earth Systems and Environment, 2024)

Towards improved conversion of wet waste to jet fuel with atomic layer deposition-coated hydrodeoxygenation catalysts - W. Wilson McNeary; Jacob H. Miller; Sean A. Tacey; Jonathan Travis; Gabriella D. Lahti; Michael B. Griffin; Katherine L. Jungjohann; Glenn Teeter; Tugce Eralp Erden; Carrie A. Farberow; Luke Tuxworth; Michael J. Watson; et al. (Chemical Engineering Journal, 2023)

Decline of anthropogenic lead in South Atlantic Ocean surface waters from 1990 to 2011: New constraints from concentration and isotope data - Arianna Olivelli; Katy Murphy; Luke Bridgestock; David J. Wilson; Micha Rijkenberg; Rob Middag; Dominik J. Weiss; Tina van de Flierdt; Mark Rehkämper (Marine Pollution Bulletin, 2023)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Population genetic structure of a broadcast‐spawning coral across a tropical–temperate transition zone reveals regional differentiation and high‐latitude reef isolation - Richard D. Evans; Luke Thomas; W. Jason Kennington; Nicole M. Ryan; Nerida G. Wilson; Zoe Richards; Ryan J. Lowe; Chenae Tuckett (Journal of Biogeography, 2021)
Aim Genetic connectivity is a key component of species resilience to climate change in terms of recovery capacity following disturbance and capacity to disperse to novel locations as the climate warms and isotherms shift poleward. We aimed to strengthen our understanding of resilience in this context by characterizing patterns of connectivity and genetic diversity in a broadcast spawning coral across a tropical–temperate transition zone. We hypothesize genetic differentiation between tropical and temperate populations and decreasing genetic diversity with higher latitudes. Location Western Australia (WA). Taxon Turbinaria species complex. Turbinaria ‘reniformis’ Oken, 1815 (Scleractinia: Dendrophylliidae). Methods A total of 930 target corals were sampled from 10 locations between 13 and 32° latitude spanning a 9°C mean temperature range. In situ species identification of T . reniformis is hindered by morphological plasticity and homoplasy with sister species. We combined Sanger sequencing of two mitochondrial DNA markers and high‐throughput genotyping by sequencing (GBS) to isolate a single genetic Turbinaria lineage from our dataset through which patterns of genetic flow and diversity along the WA coastline could be explored using population‐ and individual‐based clustering analyses. Results Mitochondrial DNA sequence variation was low among Turbinaria samples and could not resolve individual species. Using GBS, we identified three genetically distinct lineages. Subsequent analyses within one of these lineages revealed strong spatial subdivision with 2–3 genetic clusters. While temperate populations were genetically diverged from more tropical sites, we did not observe declines in genetic diversity with latitude. Main conclusions Tropical populations of T . ‘reniformis’ in Western Australia exhibit strong genetic connectivity, which extends to a southern limit at sub‐tropical Shark Bay. Temperate populations are genetically isolated from their tropical counterparts but have relatively high genetic diversity. While the maintenance of genetic variation in temperate populations may provide some resilience to future climate scenarios, their isolation may increase their vulnerability.

Artificial night light and anthropogenic noise interact to influence bird abundance over a continental scale - Ashley A. Wilson; Mark A. Ditmer; Jesse R. Barber; Neil H. Carter; Eliot T. Miller; Luke P. Tyrrell; Clinton D. Francis (Global Change Biology, 2021)
The extent of artificial night light and anthropogenic noise (i.e., “light” and “noise”) impacts is global and has the capacity to threaten species across diverse ecosystems. Existing research involving impacts of light or noise has primarily focused on noise or light alone and single species; however, these stimuli often co‐occur and little is known about how co‐exposure influences wildlife and if and why species may vary in their responses. Here, we had three aims: (1) to investigate species‐specific responses to light, noise, and the interaction between the two using a spatially explicit approach to model changes in abundance of 140 prevalent bird species across North America, (2) to investigate responses to the interaction between light exposure and night length, and (3) to identify functional traits and habitat affiliations that explain variation in species‐specific responses to these sensory stimuli with phylogenetically informed models. We found species that responded to noise exposure generally decreased in abundance, and the additional presence of light interacted synergistically with noise to exacerbate its negative effects. Moreover, the interaction revealed negative emergent responses for several species that only reacted when light and noise co‐occurred. Additionally, an interaction between light and night length revealed 47 species increased in abundance with light exposure during longer nights. In addition to modifying behavior with optimal temperature and potential foraging opportunities, birds might be attracted to light, yet suffer inadvertent physiological consequences. The trait that most strongly related to avian response to light and noise was habitat affiliation. Specifically, species that occupy closed habitat were less tolerant of both sensory stressors compared to those that occupy open habitat. Further quantifying the contexts and intrinsic traits that explain how species respond to noise and light will be fundamental to understanding the ecological consequences of a world that is ever louder and brighter.

Microbial diversity and activity in Southern California salterns and bitterns: analogues for remnant ocean worlds - Benjamin Klempay; Nestor Arandia‐Gorostidi; Anne E. Dekas; Douglas H. Bartlett; Christopher E. Carr; Peter T. Doran; Avishek Dutta; Natalia Erazo; Luke A. Fisher; Jennifer B. Glass; Alexandra Pontefract; Sanjoy M. Som; et al. (Environmental Microbiology, 2021)
Summary Concurrent osmotic and chaotropic stress make MgCl 2 ‐rich brines extremely inhospitable environments. Understanding the limits of life in these brines is essential to the search for extraterrestrial life on contemporary and relict ocean worlds, like Mars, which could host similar environments. We sequenced environmental 16S rRNA genes and quantified microbial activity across a broad range of salinity and chaotropicity at a Mars‐analogue salt harvesting facility in Southern California, where seawater is evaporated in a series of ponds ranging from kosmotropic NaCl brines to highly chaotropic MgCl 2 brines. Within NaCl brines, we observed a proliferation of specialized halophilic Euryarchaeota, which corresponded closely with the dominant taxa found in salterns around the world. These communities were characterized by very slow growth rates and high biomass accumulation. As salinity and chaotropicity increased, we found that the MgCl 2 ‐rich brines eventually exceeded the limits of microbial activity. We found evidence that exogenous genetic material is preserved in these chaotropic brines, producing an unexpected increase in diversity in the presumably sterile MgCl 2 ‐saturated brines. Because of their high potential for biomarker preservation, chaotropic brines could therefore serve as repositories of genetic biomarkers from nearby environments (both on Earth and beyond) making them prime targets for future life‐detection missions.

Acute exercise-related cognitive effects are not attributable to changes in end-tidal CO2 or cerebral blood velocity - Leena N. Shoemaker; Luke C. Wilson; Samuel J. E. Lucas; Liana Machado; James D. Cotter (European Journal of Applied Physiology, 2020)

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

Multidisciplinary investigations of the diets of two post-medieval populations from London using stable isotopes and microdebris analysis - Madeleine Bleasdale; Paola Ponce; Anita Radini; Andrew S. Wilson; Sean Doherty; Patrick Daley; Chloe Brown; Luke Spindler; Lucy Sibun; Camilla Speller; Michelle M. Alexander (Archaeological and Anthropological Sciences, 2019)

Grazing enhances belowground carbon allocation, microbial biomass, and soil carbon in a subtropical grassland - Chris H. Wilson; Michael S. Strickland; Jack A. Hutchings; Thomas S. Bianchi; S. Luke Flory (Global Change Biology, 2018)
Despite the large contribution of rangeland and pasture to global soil organic carbon ( SOC ) stocks, there is considerable uncertainty about the impact of large herbivore grazing on SOC , especially for understudied subtropical grazing lands. It is well known that root system inputs are the source of most grassland SOC , but the impact of grazing on partitioning of carbon allocation to root tissue production compared to fine root exudation is unclear. Given that different forms of root C have differing implications for SOC synthesis and decomposition, this represents a significant gap in knowledge. Root exudates should contribute to SOC primarily after microbial assimilation, and thus promote microbial contributions to SOC based on stabilization of microbial necromass, whereas root litter deposition contributes directly as plant‐derived SOC following microbial decomposition. Here, we used in situ isotope pulse‐chase methodology paired with plant and soil sampling to link plant carbon allocation patterns with SOC pools in replicated long‐term grazing exclosures in subtropical pasture in Florida, USA . We quantified allocation of carbon to root tissue and measured root exudation across grazed and ungrazed plots and quantified lignin phenols to assess the relative contribution of microbial vs. plant products to total SOC . We found that grazing exclusion was associated with dramatically less overall belowground allocation, with lower root biomass, fine root exudates, and microbial biomass. Concurrently, grazed pasture contained greater total SOC , and a larger fraction of SOC that originated from plant tissue deposition, suggesting that higher root litter deposition under grazing promotes greater SOC . We conclude that grazing effects on SOC depend on root system biomass, a pattern that may generalize to other C4‐dominated grasslands, especially in the subtropics. Improved understanding of ecological factors underlying root system biomass may be the key to forecasting SOC and optimizing grazing management to enhance SOC accumulation.

Conceptualizing Social Outcomes of Large Marine Protected Areas - Rebecca L. Gruby; Luke Fairbanks; Leslie Acton; Evan Artis; Lisa M. Campbell; Noella J. Gray; Lillian Mitchell; Sarah Bess Jones Zigler; Katie Wilson (Coastal Management, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Modeling Hurricane Exposure in a Caribbean Lower Montane Tropical Wet Forest: The Effects of Frequent, Intermediate Disturbances and Topography on Forest Structural Dynamics and Composition - Denneko Luke; Kurt McLaren; Byron Wilson (Ecosystems, 2016)

Propagule quality mediates invasive plant establishment - James A. Estrada; Chris H. Wilson; Julienne E. NeSmith; S. Luke Flory (Biological Invasions, 2016)

Restoration of Riparian Areas Following the Removal of Cattle in the Northwestern Great Basin - Jonathan L. Batchelor; William J. Ripple; Todd M. Wilson; Luke E. Painter (Environmental Management, 2015)

Combining mesocosm and field experiments to predict invasive plant performance: a hierarchical Bayesian approach - Chris H. Wilson; T. Trevor Caughlin; David J. Civitello; S. Luke Flory (Ecology, 2015)
Invasive plant fecundity underlies propagule pressure and ultimately range expansion. Predicting fecundity across large spatial scales, from regions to landscapes, is critical for understanding invasion dynamics and optimizing management. However, to accurately predict fecundity and other demographic processes, improved models that scale individual plant responses to abiotic drivers across heterogeneous environments are needed. Here we combine two experimental data sets to predict fecundity of a widespread and problematic invasive grass over large spatial scales. First, we analyzed seed production as a function of plant biomass in a small‐scale mesocosm experiment with manipulated light levels. Then, in a field introduction experiment, we tracked plant performance across 21 common garden sites that differed widely in available light and other factors. We jointly analyzed these data using a Bayesian hierarchical model (BHM) framework to predict fecundity as a function of light in the field. Our analysis reveals that the invasive species is likely to produce sufficient seed to overwhelm establishment resistance, even in deeply shaded environments, and is likely seed‐limited across much of its range. Finally, we extend this framework to address the general problem of how to scale up plant demographic processes and analyze the factors that control plant distribution and abundance at large scales.

Moving beyond the conceptual: specificity in regional climate change adaptation actions for biodiversity in South East Queensland, Australia - Luke P. Shoo; Julian O’Mara; Karin Perhans; Jonathan R. Rhodes; Rebecca K. Runting; Susanne Schmidt; Lochran W. Traill; Lui C. Weber; Kerrie A. Wilson; Catherine E. Lovelock (Regional Environmental Change, 2014)

Casuarina: biogeography and ecology of an important tree genus in a changing world - Luke J. Potgieter; David M. Richardson; John R. U. Wilson (Biological Invasions, 2014)

Syncope is unrelated to supine and postural hypotension following prolonged exercise - Carissa J. Murrell; James D. Cotter; Keith George; Robert Shave; Luke Wilson; Kate Thomas; Michael J. A. Williams; Philip N. Ainslie (European Journal of Applied Physiology, 2011)

Skin cooling aids cerebrovascular function more effectively under severe than moderate heat stress - Rebekah A. I. Lucas; Philip N. Ainslie; Jui-Lin Fan; Luke C. Wilson; Kate N. Thomas; James D. Cotter (European Journal of Applied Physiology, 2010)